Pengelompokan Destinasi Wisata di Batam Berdasarkan Daya Tarik dan Fasilitas Menggunakan Metode K-Means Clustering - Astiti, Sarah; Harman, Rika; Darmansah, D (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Batam is one of the leading tourist destinations in Indonesia, has many attractions, ranging from marine tourism, history, to shopping. However, there is no classification of tourist destinations based on the attractions and facilities available, which makes tourism development less effective. This study aims to group tourist destinations in Batam City based on tourist attractions and available facilities using the K-Means Clustering method with Rapidminer Application processing. This grouping is expected to help the government and tourism actors in designing more effective tourism development strategies that are in accordance with the characteristics of each destination group. The data used in this study consists of several tourist destinations in Batam, where the variables measured include tourist attractions (natural beauty, culture, activities, and accessibility) and facilities (accommodation, transportation, public facilities, and other supporting services). The results of the study show that there are three main groups of tourist destinations that have different characteristics, namely the destination group with high appeal and facilities is cluster_2 with 3 destinations, the middle group is cluster_1 with 1 destination, and the low group is cluster_0 with 3 destinations.